PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN, DAN KEBIJAKAN UTANG TERHADAP KINERJA PASAR DENGAN MODERASI ALIRAN KAS BEBAS - APRILYCIA WIYONO, ARIESTA (Universitas Katolik Widya Mandala Surabaya, 2012)
Each company which listing in BEI (Indonesia Stock xchange) expected to have good market performance, which indication with stock return increasing from year to year. But that way, not all company can realize the expectation. Theoretically, market performance can be improved to through profitability, dividend policy, debt policy, and free cash flow as moderately. Target of this research, that is: (1) Testing influence of profitability, dividend policy, and debt policy to market performance. (2) Testing ability of free cash flow strengthen influence of profitability, dividend policy, and debt policy to market performance. This research use hypothesis and its type is causal research. Research data taken from secunder data that is ICMD (2007-2010) and financial statement of emiten. Using sample counted 18 company which selected with purposive sampling technique. Technique analyse data multiple regression with moderator effect. Result of this research indicate that: (1) Profitability and debt policy have a significant positive effect to market performance, while dividend policy has not a significant effect to market performance. (2) Free cash flow can strengthen influence of profitability and debt policy to market performance significantly. On the contrary, free cash flow unable to strengthen influence of dividend policy to market performance significantly.